A Comparative Analysis on the Cham Muslims’ Religious Life in the Borderland of An Giang and Tay Ninh Provinces - Hoang Van Chung; Tran Thi Phuong Anh, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The land border region of Vietnam is characterized by distinctive features related to geography, ethnic settlement, and levels of economic, cultural, and social development. These features have a certain influence on the presence, operation, and impact of religion on both the material and spiritual aspects of daily life. Approaching the topic from the disciplines of religious studies and sociology, and based on an analysis of both qualitative and quantitative data, this article focuses on comparing and elucidating some fundamental aspects of the religious life of the Cham Muslims in the border region of two provinces An Giang and Tay Ninh. The study explores the challenges these communities face, particularly in balancing their religious practices with the demands of modern economic, cultural, and social life.Received 15th November 2024; Revised 5th February 2025; Accepted 7th April 2025